Evaluation of Serum and Salivary Interleukin-6 as Biomarkers for Early Detection of Oral Cancer - Babkair, Hamzah Ali (Bangladesh Journal of Medical Science, 2026)
Background Late-stage diagnosis is primarily responsible for the high morbidity and death rates linked to oral squamous cell carcinoma (OSCC). Improving patient outcomes requires the creation of trustworthy, non-invasive biomarkers for early detection. The multifunctional pro-inflammatory cytokine interleukin-6 (IL-6) has been linked to carcinogenesis, but further research is needed to determine how well it can diagnose early-stage OSCC, particularly in saliva. Methods 60 participants participated in a case-control study, 30 of whom had just been diagnosed with early stage (Stage I & II) OSCC that was histopathologically verified, and 30 of whom were healthy controls who were matched for age and gender. Samples of venous blood and unstimulated entire saliva were obtained. A commercially available enzyme-linked immunosorbent assay (ELIAs) kit was used to determine the levels of IL-6. Using receiver operating characteristic (ROC) curve analysis, the diagnostic performance was ascertained. Results The OSCC group had substantially greater serum and salivary IL-6 levels than the control group (p < 0.001). In OSCC patients, the mean serum IL-6 level was 12.5 +/- 3.1 pg/mL, whereas in controls, it was 4.2 +/- 1.5 pg/mL. In OSCC patients, the mean salivary IL-6 level was 18.7 +- 4.2 pg/mL, whereas in controls, it was 5.1 +- 1.8 pg/mL. With an area under the curve (AUC) of 0.94 (95% CI: 0.88-1.00) compared to serum IL-6 (AUC = 0.88, 95% CI: 0.79-0.97), ROC analysis revealed salivary IL-6 to be a superior diagnostic marker. Salivary IL-6 demonstrated 90.0% sensitivity and 93.3% specificity for identifying OSCC at an ideal cut-off of 11.5 pg/mL. Conclusion Compared to serum IL-6, salivary IL-6 exhibits greater diagnostic performance and is significantly higher in individuals with earlystage OSCC. Salivary IL-6 is a potential biomarker for the early identification and screening of oral cancer because of its noninvasive nature, high sensitivity, and specificity. By acting early, it may be possible to improve the prognosis. Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue 2026, Page : S114-S118